Progress of research on the application of central venous catheterization (中心静脉置管技术应用研究进展) - FAN Lili (范丽丽) (Association of Integrative Nursing, 2023)
With its rapid development, central venous catheterization has been widely used in long-term intravenous nutrition, chemotherapy, dialysis, and emergency rescue of emergency and critical patients. Meanwhile, the assisted puncture point and tip positioning technology has been improved as well. It has developed from empirical blind puncture to intracavity electrocardiogram-guided catheterization, CGW conductive wire navigation and positioning system, digital subtraction angiography-guided catheterization, and transesophageal ultrasound-guided catheterization. This paper reviews the progress of the application of central vein catheterization and the use of the identical body unit method in the field of integrated traditional Chinese and western medicine. It discusses the application prospect of the identical body unit method in central venous catheterization to determine a simple, practical, and reliable method that is not less accurate than the current common practice, sees no significant increase in the incidence of complications and can be popularized in grass-roots hospitals. (中心静脉置管技术在临床应用广泛, 同时穿刺点及尖端定位辅助技术快速发展, 已由经验性盲穿发展为腔内心电图引导下置管技术、CGW电导丝导航与定位系统、数字减影血管造影引导下置管和经食管超声引导下的置管技术。本文对中心静脉置管技术应用进展和同身寸法在中西医结合领域的应用进行综述, 初步探讨同身寸法作为一种辅助技术在中心静脉置管中应用前景, 旨在为提高穿刺成功率、减少穿刺盲目性、保证穿刺安全性提供参考。)